Clinical importance of circulating immune complexes in human acute lymphoblastic leukemia - Croce, María Virginia (1985)
A total of 122 sera from acute lymphoblastic leukemia (ALL) patients were analyzed for circulating immune complexes (CIC) by two methods: the 125I-C1q binding assay and the polyethylene glycol precipitation test (PEG). The results were correlated with induction, remission and relapse stages of the disease. Using the first method the levels of CIC in induction were 15.18±9.15, with 19/29 positive cases (65.50%), P<0.001 compared with controls. In the remission phase the levels were 9.02±5.62, 11/45 (24.49%) nonsignificant P value, and in relapse they were 16.14±11.17 28/48 (58.33%) P<0.001. The PEG precipitation test results were: 0.33±0.10, 8/22 (36.36%); 0.24±0.11, 10/48 (20.83%) and 0.28±0.10, 6/28 (21.42%), respectively. Thus the values of CIC as measured by PEG in the three clinical of phases ALL did not differ significantly from controls. This contrasts with results obtained by the radioiodinated C1q binding assay, where the incidence of positive values was significantly higher in induction and in relapse and lower in the remission phase. These observations were extended in sequential vertical studies performed in a group of patients. These results suggest that raised CIC detected by the 125I-C1q method may reflect a progressive state in ALL and that quantitation of these immune complexes may provide an adequate biochemical marker for prognosis.